2011
DOI: 10.1063/1.3641417
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization mechanisms and recording characteristics of Si/CuSi bilayer for write-once blu-ray disc

Abstract: The crystallization mechanisms of Si/CuSi bilayer and its recording characteristics for write-once blu-ray disc (BD-R) were investigated. It was found that Cu3Si phase appeared during the room temperature sputtered deposition. Then, the Si atoms in CuSi layer segregated and crystallized to cubic Si in Cu3Si nucleation sites as the film was annealed at 270 °C. After heating to 500 °C, the grains size of cubic Si phase grew and the hexagonal Si phase was observed. The dynamic tests show that the Si/CuSi bilayer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 13 publications
1
7
0
Order By: Relevance
“…Particularly in Ref. [15] and [17], also Cu 3 Si is reported to form at room temperature. After a brief (5-10 min) annealing at 438 K, we found the described asymmetry to be even more pronounced (see Fig.…”
Section: Sample Preparationmentioning
confidence: 95%
“…Particularly in Ref. [15] and [17], also Cu 3 Si is reported to form at room temperature. After a brief (5-10 min) annealing at 438 K, we found the described asymmetry to be even more pronounced (see Fig.…”
Section: Sample Preparationmentioning
confidence: 95%
“…It can be found that the GeCu layers had high optical contrast (at a wavelength of 405 nm), revealing that these films possess promising potential for blue laser recording media. Recently, Si/metal-silicide films including Si/CuSi [13] and Si/NiSi [14] have been presented in our previous works, employed as the recording layers of BD-R. The results reveal that better disc performance can be obtained in the Si/metal-silicide BD-R.…”
Section: Introductionmentioning
confidence: 97%
“…Except for the metal/a-Si recording films, the other layer structure of the recording film applied for the BD-R was proposed in our previous research, i.e., the metal-silicide/a-Si bilayer films [11,12]. In 2011 and 2014, we presented the Si/CuSi and Si/NiSi bilayer recording films of BD-Rs, respectively [11,12].…”
Section: Introductionmentioning
confidence: 99%